OVERCOME LAND DEGRADATION WITH SOIL AMELIORANT APPLICATION (STUDY OF FARMER PERCEPTIONS IN MALANG, EAST JAVA) - S. H. Tala'ohu; M. Al-Jabri (Institut Teknologi Bandung, 2008)
Improving the quality of soils degradation can be achieved using the soil ameloirant (i. e. Zeolite, manure, compost, etc.), conservation farming systems, organic management, system balanced fertilization specific location, and efficiency of water use. This study aimed to determine: (1) the type of soil ameloirant that is still used by farmers, sources of information, and its use of doses, (2) constraints and benefit of use, (3) fertilizer efficiency, and (4) development opportunities. This study conducted by survey method that is structured interview included: farmer characteristics, identification, and soil ameloirant development prospects in the future. Identification of soil ameloirant, such as: type of soil ameloirant used by farmers, sources of information, applications, the impact of the use, benefits and constraints of use. The results showed that: the distribution age of respondent â‰¤ 55 years (80.7%) and > 55 years (19.3%). Dissemination through counseling, pilot project on farmers land in order to developing the confidence of farmers will benefit and importance of the use soil ameloirant to repair land degradation, increasing productivity, and agricultural production. The soil ameloirant have been used by 24% of respondents farmers is zeolite granules (Agro-88) and dolomite; measurement of soil ameloirant for rice field: 500 kg of zeolit /ha and 577 kg dolomite/ha; garden: 219 kg zeolite/ha and 409 kg dolomite/ ha; mixedgarden: 600 kg of zeolit/ha and 143 kg dolomite/ha. Soil ameloirant benefits is for increasing the production: paddys, corns, and vegetables (cauliflower, peppers, tomatoes) around 10-30%, improving the soil fertility and reducing dosage of urea fertilizer as much as 15-30% and SP-36 as much as 30%.